A Review of Verb Network Strengthening Treatment: Theory, Methods, Results, and Clinical Implications. Issue 2 (April 2016) - Edmonds, Lisa A.
Abstract : This article examines Verb Network Strengthening Treatment (VNeST), a relatively new treatment approach for anomia in people with aphasia. The VNeST protocol aims to promote generalization to increased lexical retrieval of untrained words across a hierarchy of linguistic tasks, including single-word naming of nouns and verbs, sentence production, and discourse. The concept of the verb network relates to the centrality of the verb to the semantics and syntax of a sentence. The VNeST protocol elicits diverse agents (e.g., musician ) and patients (e.g., tambourine ) around trained verbs (e.g., shake ) to activate a range of semantic concepts and personal responses to potentially facilitate generalization to a multitude of lexical items. The pre- and posttreatment generalization results for the 19 participants reported in English are analyzed. Participants represent a range of aphasia severities and types, including Broca's, transcortical motor, anomic, Wernicke's, and conduction aphasia. A previous study that evaluated 3 monolingual Korean speakers on a modified version of VNeST that accommodated Korean's verb final word order is also summarized. The findings across the 5 English studies and the Korean study revealed increased noun and verb naming and lexical retrieval in sentences and discourse on untrained items and tasks for more than half of the participants, suggesting preliminary efficacy for VNeST. Potential predictors and mechanisms of improvement are explored, and clinical implications, including consideration of goals, outcome measures, dosage, inclusion and evaluation of writing, and verb selection, are discussed.